Pharmacological Evaluation of Trichosanthese Dioica for Management of Alzheimer and Other Dementia Disorders - Sharma, Sarika; Sharma, Anshu (Journal of Neonatal Surgery, 2025)
Investigate the compound’s ability to inhibit acetylcholinesterase, which could contribute to memory enhancement by performing the in-vitro and in-vivo activity. By achieving these objectives, the research will contribute to identifying new, natural therapeutic options for memory enhancement and the treatment of cognitive decline. Additionally, it may pave the way for further studies on the use of Trichosanthese dioica and other herbal compounds in brain health. Pharmacological evaluation of cucurbitacins (B and E) extracted from T.dioica for Antialzhiemer’s approach 3 core Invivo and invitro evaluation study were done for neuroprotective, antioxidant, and acetylcholinesterase inhibition. Both Cucurbitacin B and E exhibited multi-targeted protective effects against Alzheimer’s disease in vitro. They improved cell viability (MTT assay), reduced oxidative stress (DCFDA), decreased inﬂammatory cytokines (ELISA), and inhibited AChE (Elman’s method). Among the two, Cucurbitacin E consistently showed superior performance, highlighting its promise as a neuroprotective agent for Alzheimer’s therapy.The combination treatments (Donepezil + Cucurbitacin B or E) showed the most effective reduction in ROS, indicating that these compounds might work together to attenuate oxidative stress. The combination groups (CB+Donepezil and CE+ Donepezil) showed slightly lower TNF-α and IL-6 levels than Donepezil alone, Donepezil (78.6%) and Cucurbitacin E (76.4%) signiﬁcantly restored alternation behavior. Cucurbitacin B (65.8%) also improved performance, though to a lesser extent. Cucurbitacin E emerges as a more potent neuroprotective agent than Cucurbitacin B, offering a strong rationale for its further development as a natural therapeutic lead in Alzheimer’s disease management. This study not only validates the ethno pharmacological use of Trichosanthese dioica but also provides a scientiﬁc foundation for the pharmacological advancement of Cucurbitacin based compounds.